Master sahib - Khalida ·, Afsar (Book Group Pakistan, 1994)
"Master Sahib" by Khalida Afsar is a poignant story that explores the emotional and social struggles of a teacher, highlighting themes of sacrifice, dedication, and the impact of education on both individuals and society.